2018
DOI: 10.1111/1365-2664.13278
|View full text |Cite
|
Sign up to set email alerts
|

Assessing bottom trawling impacts based on the longevity of benthic invertebrates

Abstract: 1. Bottom trawling is the most widespread human activity directly affecting seabed habitats. Assessment and effective management of the effects of bottom trawling at the scale of fisheries requires an understanding of differences in sensitivity of biota to trawling. Responses to disturbance are expected to depend on the intrinsic rate of increase in populations (r), which is expected to be linearly related to the reciprocal of longevity. We examine the relationship between the longevity of benthic invertebrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 30 publications
1
57
0
1
Order By: Relevance
“…A further extension of this research has shown that taxon longevity predicts recovery rate (Rijnsdorp et al 2018;Hiddink et al 2019). The latter finding concurs with expectations based on our understanding of the likely response of long-lived species.…”
Section: Quantification Of the Aggregated Effects Of Fishing Disturbasupporting
confidence: 89%
See 1 more Smart Citation
“…A further extension of this research has shown that taxon longevity predicts recovery rate (Rijnsdorp et al 2018;Hiddink et al 2019). The latter finding concurs with expectations based on our understanding of the likely response of long-lived species.…”
Section: Quantification Of the Aggregated Effects Of Fishing Disturbasupporting
confidence: 89%
“…Some have rejected the notion that bottom trawling could ever be considered "sustainable" (Watling and Norse 1998). This debate highlights the need to better understand the resilience of habitats and communities to different levels of trawl activity with the goal of informing management and operational practices that might mitigate the effects of trawling on the seabed environment (e.g., Lambert et al 2014;Eigaard et al 2017;Pitcher et al 2017;Hiddink et al 2019). Irrespective of the philosophical considerations of what amount of trawling activity is, or is not, sustainable, there now exist numerous international and national policies that require the scientific community to assess the impacts of bottom fishing in relation to the maintenance of marine biodiversity, essential fish habitats, and other marine ecosystem processes (Friedman et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Brief examples and performance‐based analyses are used to develop guidance on best practices for a wide range of fisheries and associated management systems. Building on previous analyses of the impacts and management of trawling activities (Collie et al, ; Hiddink et al, , ; Pitcher et al, ; Sciberras et al, ), we address multiple knowledge gaps identified in a prioritization exercise concerned with reducing the environmental impacts of trawling (Kaiser et al, ). The resulting guidance on best practices is intended to help managers and the industry minimize environmental impacts of trawling per unit weight or value of landed fish, while achieving a sustainable level of fish production.…”
Section: Introductionmentioning
confidence: 99%
“…The subsequent recovery of the bioturbation was modelled based on the logistic growth equation (Eq. 4), with the recovery rate (r) the inverse of the longevity of the species community, kept constant at 0.04 y -1 (Rijnsdorp et al, 2016;Hiddink et al, 2019).…”
Section: Disturbance Modellingmentioning
confidence: 99%